Understanding Entrepreneurial Orientation based Research: A Proposed New Theoretical Framework - Surin, Ehsan Fansuree; Edward, Oswald Timothy; Shaaran, Sayuthi; Ngah, Rohana (Information Management and Business Review, 2023)
Entrepreneurial orientation-based research is reviewed and in-depth examined especially in the entrepreneurship theme. Research on the impact of entrepreneurial orientation (EO) on organizational performance has generated numerous important findings. Despite abundant attention given to research on the relationship between entrepreneurial orientation and organizational performance, the results are still inconsistent. Current progress on entrepreneurial orientation-based research is lacking in terms of theoretical integration therefore unable to produce a unified framework. This paper reviews the literature review thoroughly to build a novel theoretical framework that proposes the linkages of entrepreneurial orientation, innovation management, business environment as well as organizational performance. By using resource-based view (RBV) and contingency theory, the relationship between the variables has been established. The proposed unified theoretical framework will provide useful insight into the direct impact of entrepreneurial orientation on organizational performance. Moreover, the direct relationship is moderated by two variables namely innovation management and business environment. This unified theoretical framework would benefit from an amalgamation between process and outcome-oriented research in the entrepreneurship field.